Tourist Mobility and Destination Loyalty: Insights for Hospitality and Tourism Management in Indonesia - Aulia, Zahra Khoironi; Amanda, Dian Mita; Asshofi, Izza Ulumuddin Ahmad (Journal of Gastro Tourism, 2025)
Tourism represents one of the fastest-growing sectors globally. In Indonesia, this growth is reinforced by abundant natural resources, cultural diversity, and substantial tourism capital, which collectively strengthen the country’s position as a prominent tourist destination. The Central Bureau of Statistics (BPS) recorded tourist arrivals to Indonesia in 2024 at 13.9 million or grew by 19.05% from the previous year. Majority of tourists came from ASEAN countries (Ministry of Tourism, 2025). The purpose of this study is to analyze tourist mobility and destination loyalty in the context of hospitality and tourism management in Indonesia. This article focuses on the economic aspect and tries to explain how tourist mobility contribute the economic growth of Indonesia's local areas. This research also aims to find and investigate methods that can help increase the role of tourism sector in supporting the economy. The type of research used in this research is descriptive qualitative research with a systematic literature review approach. The results showed that local destinations in Indonesia are very influential on the Indonesian economy. The factors that influence domestic tourists' loyalty to local destinations include destination attractiveness, accessibility, diversity, information, hospitality, cleanliness, accommodation and relative prices.